Synthesis of polypropylene functionalized with a trace amount of reactive functional groups and its utilization in graft-type nanocomposites. (5th December 2018) - Kurahashi, Eiji; Wada, Toru; Nagai, Takeshi; Chammingkwan, Patchanee; Terano, Minoru; Taniike, Toshiaki
Abstract: In the preparation of polypropylene (PP)-based nanocomposites, grafting end-functionalized PP to nano-sized fillers is a promising strategy to alleviate the compatibility and interfacial problems at once, while poor synthetic efficiency for the end-functionalized PP and its grafting has been a major issue to be addressed. Here, we synthesized functionalized PP with one or less silicon methoxy groups per chain by means of direct copolymerization using a Ziegler-Natta catalyst, and utilized it as a reactive matrix in melt-mixing with spherical SiO2 nanoparticles. In addition to its synthetic advantage, the introduction of a trace amount of reactive functional groups delivered several profitable consequences to the nanocomposites that are typical for end-functionalized PP, such as improved dispersion, dramatically accelerated crystallization, and mechanical reinforcements. Graphical abstract: Highlights: A trace amount of reactive groups was introduced into PP by copolymerization. The functionalized PP as a reactive matrix was in-situ grafted to SiO2 nanoparticles. The functionalized PP behaved like an end-functionalized PP in the nanocomposites.